2020
DOI: 10.5965/223811711912020073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the growth and morpho-physiological performance of three cultivars of Colombian quinoa grown under a greenhouse

Abstract: Quinoa (Amaranthaceae) is a native pseudo-cereal produced throughout the South American zone, where it is used in the preparation of food and as a promising alternative for the colonization of edaphoclimatic areas affected by anthropic and natural factors. Among the main problems that affect crop production, we can include those related to growth, development and production, generated by limitations of adaptability of new cultivars in specific areas. For this reason, this research intended to analyze the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…This is consistent with what was reported by García‐Parra, Stechauner‐Rohringer, et al. ( 2020 ) and García‐Parra, Zurita‐Silva, et al. ( 2020 ), who indicated that the environmental temperature plays an important role in the phenological phases prior to the development of the seed, influencing productive and compositional aspects.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with what was reported by García‐Parra, Stechauner‐Rohringer, et al. ( 2020 ) and García‐Parra, Zurita‐Silva, et al. ( 2020 ), who indicated that the environmental temperature plays an important role in the phenological phases prior to the development of the seed, influencing productive and compositional aspects.…”
Section: Resultssupporting
confidence: 93%
“…Subsequently and in accordance with Ticona et al. ( 2022 ), the natural geographic distribution of the species extends from 5° north latitude in southern Colombia (García‐Parra, Stechauner‐Rohringer, et al., 2020 ; García‐Parra, Zurita‐Silva, et al., 2020 ; Manjarres‐Hernández & Morillo‐Coronado, 2022 ) to 43° south latitude in the Tenth Region of Chile (Fuentes et al., 2012 ) and Argentina (Vidueiros et al., 2015 ), while the altitudinal distribution ranges between 0 and 4000 m.a.s.l. Thus, quinoa crops have a high adaptability to different agroclimatic conditions, making them one of the crops with the best productive potential to be adopted by small producers with a great contribution to food safety (Bazile et al., 2015 ; Camaggio, 2014 ; Garcia et al., 2018 ).…”
Section: Introductionsupporting
confidence: 76%
“…In general, the accessions with plant heights higher than average (>176.7 cm) presented lower yields, as reported by [ 13 ]), who, when evaluating quinoa materials in southern Italy, found negative correlations between plant height and yield. [ 14 ] also observed a decrease in growth with the formation of grains in the Department of Cauca, Colombia in the Tunkahuan, Blanca de Jericó, and Blanca de Soracá varieties. This was probably due to the fact that the increase in plant growth coincides with the beginning of the reproductive stage, where the energy produced by plants is distributed in the growth and the beginning of panicles.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of the central region of Colombia, quinoa cultivars such as Tunkahuan, Soracá and Blanca Jericó were identified, which present a variation in the duration of the phenological cycles under cold weather conditions [15,16] and may be directly associated with temperature and precipitation, influencing variables such as grain yield, harvest index, biomass and phenological time, as has already been reported in other researches [17,18]. However, there is still a lack of knowledge about the effect that the altitude gradient may have on physiological activity parameters in Colombian quinoa cultivars, so our working hypothesis was that the altitude gradient has a differential effect on the physiological performance of seven quinoa cultivars.…”
Section: Introductionmentioning
confidence: 99%